Nonlinearity and Functional Analysis : Lectures on Nonlinear Problems in Mathematical Analysis - Berger, Melvyn S. (New York : Academic Press, 1977)
The material to be described in this text is divided into three parts, with each part containing two chapters. Part 1 is concerned first with the motivation and preliminary mathematical material necessary to understand the context of later developments in the book and second with providing a rudimentary calculus and classification of non-linear operators. Part 2 deals with local analysis. The third and final part of the book describes analysis in the large and shows the necessity of combining concrete analysis with transcendental methods. A main object of the text is the application of the abstract results obtained to resolve interesting problems of geometry and physics.
Includes index.
Bibliography: p. 399-408.
ne 08/03/2018
Loan
Keywords: Mathematical Analysis; Functional Analysis; Nonlinear Theories